2011
DOI: 10.1093/mutage/ger076
|View full text |Cite
|
Sign up to set email alerts
|

An adaptation of the human HepaRG cells to the in vitro micronucleus assay

Abstract: The in vitro micronucleus test is considered as an attractive tool for genotoxicity testing of chemicals because of its simplicity of scoring and wide applicability in different cell types. However, most of the cells currently in use are devoid of the enzyme equipment required for activation of promutagens in the genotoxic metabolites. We postulated that the human HepaRG cell line, which can express xenobiotic metabolising enzymes at levels close to those found in primary human hepatocytes and has retained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In agreement, we observed that malathion and isomalathion did not cause any cell loss in HepG2 cells when using the same range of concentrationsas those used for HepaRG cells. These results support our previous data showing that HepaRG cells are much more sensitive to compounds requiring liver metabolism to exert their toxic effects than HepG2 cells that did not express most of the major cytochromes P450 [21,26].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement, we observed that malathion and isomalathion did not cause any cell loss in HepG2 cells when using the same range of concentrationsas those used for HepaRG cells. These results support our previous data showing that HepaRG cells are much more sensitive to compounds requiring liver metabolism to exert their toxic effects than HepG2 cells that did not express most of the major cytochromes P450 [21,26].…”
Section: Discussionsupporting
confidence: 92%
“…Genotoxic effects of malathion and isomalathion either individually or combined, were evaluated by the micronucleus assay as previously described [21]. Briefly, after 24 h of treatment with pesticides, followed by a 72h epidermal growth factor (EGF) stimulation corresponding to the recovery time, HepaRG cells were fixed for 10 min in …”
Section: Micronucleus Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Green to blue colour indicates increasing consumption. until now, were exclusively performed in serum-supplemented medium and usually these studies did not exceed 2 weeks of cultivation after the differentiation of the HepaRG cells (Antherieu et al, 2011;Josse et al, 2012). Since HepaRG cells show stable CYP activity, they may be reliably applied in long-term repeated dose toxicity studies especially in the assessment of metabolism mediated adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethylsulfoxide (DMSO) is essential for the differentiation of HepaRG cells and induction of CYP expression (Gripon et al, 2002;Hoekstra et al, 2011). Studies that involve HepaRG cells are routinely carried out in medium containing high DMSO concentrations (≈2%) and in the presence of fetal bovine serum (FBS) (Josse et al, 2012;Leite et al, 2012). As a result of undefined composition and batch-to-batch variations, the use of FBS poses a problem in reproducibility and standardization (Hahne and Reichl, 2011).…”
Section: Introductionmentioning
confidence: 99%